The Influence of Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on Firm Value at PT Indocement Tunggal Prakarsa Tbk 2010-2019 Period - Noryani (Journal of Research in Business, Economics, and Education, 2020)
This study aims to determine the effect of Dividend Payout Ratio (DPR), the effect of Debt To Equity Ratio (DER), the effect of Return On Assets (ROA) on firm value at PT. Indocement Tunggal Prakarsa, and Dividend Payout Ratio (DPR), Debt To Equity Ratio (DER), Return On Assets (ROA) simultaneously to company value at PT Indocement Tunggal Prakarsa. This research method used is descriptive quantitative method where this research will provide an overview and explain the state of the company with data in the form of numbers which are then described and the results will be a conclusion. The sample used in this study is in the form of financial statements (balance sheet and income statement) at PT Indocement Tunggal Prakarsa Tbk in 2010 to 2019. The data analysis used in this research is financial ratio analysis, descriptive analysis, classic assumption test, multiple linear reegression, determination coefficient, correlation coefficient, and hypothesis testing and is processed using SPSS version 25. Based on the results of multiple linear regression testing Y = - 5,627 + 0,006X1 + 33,148X2 + 0,201X3 means that if the independent variable is 0, then the company value has a value of -5,627. The correlation coefficient between the variable Dividend Payout Ratio (DPR), Debt To Equity Ratio (DER), Return On Assets (ROA) on firm value based on the results of testing the relationship is very strong. And based on the hypothesis test that partially Dividend Payout Ratio (DPR) does not have a significant effect on firm value with a value of 0.131, Debt To Equity Ratio (DER) has a significant effect on firm value with a value of 0.017, Return On Assets (ROA) has significant influence on firm value with a value of 0.004. Simultaneously the Dividend Payout Ratio (DPR), Debt To Equity Ratio (DER), Return on Assets (ROA) has a significant effect on firm value with a value of 0.010. The independent variable Dividend Payout Ratio (DPR), Debt To Equity Ratio (DER), Return On Assets (ROA) explains the effect on firm value of 74.3% while the remaining 25.7%.